Determinan Profitabilitas Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Eny Maryanti (Journal of Accounting Science, 2020)
This study aims to determine whether company size moderates the effect of current ratio, environmental performance and debt to equity ratio on the profitability of consumer goods industry companies found on the Indonesia Stock Exchange (IDX). The period of this research is 2017-2019. The study population includes all consumer goods industry companies found on the Indonesia Stock Exchange (IDX) for the period of 2017-2019. The sampling technique used was purposive sampling. The research population data were 114 companies, and obtained a sample of 45 companies. The data analysis method used is SmartPLS 3 (Partial Least Square). The results of this study indicate: company size can moderate the effect of current ratio, environmental performance and debt to equiy ratio to profitability, firm size weakens the influence of current ratio to profitability, company size weakens the influence of environmental performance on profitability, firm size weakens the influence of debt to equity ratio to profitability. The moderation variable in this study is included in the pure moderation variable (pure moderation) because the moderating effect 1,2,3 has an effect on profitability while the moderating variable (company size) has no effect on profitability.